A two-neuron system for adaptive goal-directed decision-making in Lymnaea - Michael Crossley (Nature Portfolio, 2016)
Integrating information from both the external environment and an organism's internal state is an important aspect of feeding-related decision making. Here, the authors identify a two neuron circuit within the mollusc Lymnaeathat adapts feeding behaviour according to food availability and motivational state.